ANALYSIS OF FOREIGN EXPERIENCE IN CREATING A SINGLE REAL ESTATE REGISTER IN UKRAINE - Stupen Н.; Sai В.; Ryzhok З.; Bielikova Н.; Bielikov Е. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
The foreign experience of Lithuania has been studied in order to consider the possibility of merging the real estate register and land cadastre in Ukraine into a single register of real property rights. The task is to analyze the benefits of the introduction of a single register of real rights to immovable property of Ukraine, which will include, in particular, technical information. It has been established that most state registers in Lithuania are maintained by the Center of Registers, which is a state-owned enterprise. It evaluates real estate for taxation, publishes open data on real estate, namely the energy efficiency of real estate, performs an actual analysis of the real estate market according to the data contained in its databases. Today, the main registers in Lithuania are the register of real estate and cadastre, the register of legal entities, the register of addresses and the register of residents. In turn, the main functions of the register of cadastre and real estate are to register real estate, material rights and legal facts; make cadastral measurements of real estate; perform inspections of cadastral cases, enter data into the cadastre database; organize and perform real estate market research; perform individual and mass (for taxation) real estate appraisal; compile and publish maps of cadastre, real estate and real estate values; prepare statistical data from the real estate register and real estate appraisal for publication; provide data from the register and real estate cadastre, geodata, maps, as well as information on market surveys for the governmental agencies, individuals and legal entities. Thus, the consolidation of state information resources in one place, a well-considered concept of building registers allows not to duplicate data in different registers, and to obtain information from each of them in the part for which the register is responsible. Taking into account the experience of Lithuania, Ukraine also needs to create a single real estate register, which will contain both technical and legal information on all real estate objects in the country that will be convenient for both the state and ordinary citizens, as it will simplify the registration procedure of real estate property.